An introduction to the use of time analyser software to measure computer use - Schaper, Louise; Pervan, Graham (Griffith University, 2005)
This paper reports on the use of time-use software to measure actual computer use. The software was employed as part of a case study on individual use and acceptance of information and communications technology in the health sector. When compared with other methods of measurement such as self-report, the application proved to be a comprehensive and accurate source of objective information and a reliable method of measuring actual computer usage. Results also demonstrate the importance o qualitative methodologies in information systems research. Limitations of the application as a measurement tool are discussed as well as recommendations made for further investigation.